Kelas Gitar Akustik Berbasis Pembelajaran Kooperatif - Riyan Hidayatullah; Prisma Tejapermana (Gondang: Jurnal Seni dan Budaya, 2020)
This article examines learning acoustic guitar in formal schools employing cooperative learning design. The problem is focused on students’ perceptions of the difficulty of interpreting theory, teacher mastery of music theory, and the learning methods used. This study aims to describe the cooperative learning method implemented in acoustic guitar classes at schools (N = 30). Data were collected through observation, interviews, and documentation to be analyzed qualitatively using an interactive model (Miles et al., 2014). The guitar learning process is carried out in groups by breaking the home group and the expert group. Music material in group interaction is in the form of theory and practice. Based on observations of students’ musical abilities, there is an increase in knowledge of music theory and practice in guitar classes. Students receive the highest score on the aspects of sound accuracy, chord progression to the song, and the time expended learning the song. This study concludes that learning acoustic guitar applying cooperative learning methods is effective in enhancing students’ musical understanding through appreciation and creation. Appreciative attitude turns out as a manifestation of a positive response affective.